2003
DOI: 10.1081/erc-120025041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Estriol on the Proliferation and Differentiation of Human Osteoblastic MG‐63 Cells

Abstract: Estriol has been showed to prevent bone loss in osteoporotic rats and postmenopausal women, but the mechanisms remain unclear. In the present study, we evaluated the effect of estriol on osteoblastic MG-63 cells in vitro, and compared its action with 17beta-estradiol (E2). Cell proliferation was determined by measuring total cell numbers and [3H]thymidine incorporation. Cell function was studied by measuring alkaline phosphatase (ALP) activity and secreted osteocalcin. Our data showed that estriol stimulated M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 14 publications
1
22
1
Order By: Relevance
“…1). In the control cells (C), ERa and ERh proteins were both expressed, which is consistent with previous reports (Vidal et al, 1999;Luo and Liao, 2003). When the cells were treated with E 2 or isoflavone standards, ERa expression was markedly increased.…”
Section: Expression Of Estrogen Receptor a And Bsupporting
confidence: 91%
“…1). In the control cells (C), ERa and ERh proteins were both expressed, which is consistent with previous reports (Vidal et al, 1999;Luo and Liao, 2003). When the cells were treated with E 2 or isoflavone standards, ERa expression was markedly increased.…”
Section: Expression Of Estrogen Receptor a And Bsupporting
confidence: 91%
“…The effect of estrogens on proliferation has been well studied in other cellular systems, such as breast cancer cells [Mousavi and Adlercreutz, 1992;Chalbos et al, 1982;Hurd et al, 1997] and osteoblasts [Luo and Liao, 2003]. However, other reports have shown that estrogen treatment of breast cancer cells results in growth arrest [Seeger et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…ALP activity is dependent upon both ERK pathway and ER activation in MG-63 cells (Prouillet et al 2004). Estriol stimulated MG-63 cells proliferation via ER and prevented bone loss (Luo & Liao 2003). Equol, a phytoestrogen, promoted the bone formation increasing ALP activity and the MG-63 cells proliferation through ER activation (Wang et al 2014).…”
Section: Discussionmentioning
confidence: 99%